PENGEMBANGAN APLIKASI MANAJEMEN REMOTE LABORATORY MENGGUNAKAN METODE RESTful WEB SERVICE BERBASIS MOBILE - Mebiyantara, Febrian; Faisol, Ahmad; Ariwibisono, FX. (Institut Teknologi Nasional Malang, 2021)
Remote laboratory is a software environment that supports remote experiment activities, where users who are located at a far distance are allowed to interact with measurement devices and real laboratory equipment. The majority of remote laboratories that exist today are implemented with desktop computers. Computer-based systems have disadvantages that is large consumption of electrical energy and expensive equipment investment costs. Mobile applications can be an alternative so that energy and equipment investment costs can be further reduced and can make it easier to manage remote laboratory access because of its nature that can be used anytime and anywhere. This application was developed to remote red Pitaya's oscilloscope and signal generator. The access management system for this tool use RESTful Web Service technology so that data transfers are faster and consume relatively small data sizes. To remote a this tool, this application uses a webview plugin to display the simulator that is accessed via IP that has been provided by the tool. Based on the results of the development in this study, there are 6 main functional needs and 2 non-functional needs. Based on the test, it can be concluded that the development of remote laboratory management applications using the mobile-based RESTful web service method has met the criteria according to the design.